Editorial - Sirkeci, Ibrahim (Border Crossing, 2020)
On behalf of the editorial team of Border Crossing journal, I am pleased to introduce the first issue of the tenth volume. Border Crossing aims to offer a multidisciplinary venue for sharing interesting and novel research from any fields of Social Sciences and Humanities. The “open issue” model we have started last year seems appreciated by authors and readers as it allows us to release the articles once they are through the peer-review process and finalised without delay which is normally the case for most journals. In this issue, we bring four articles and a book review to you.